2015
DOI: 10.1016/j.mmcr.2015.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive cutaneous zygomycosis caused by Apophysomyces variabilis in an immunocompetent child

Abstract: A zygomycetous fungus was observed in a biopsy of a 9-year-old male. The patient was presented with severe cutaneous lesions subsequent to a traumatic car accident. Following fungal detection, antifungal treatment was prescribed but condition deteriorated rapidly and above knee amputation was done as lifesaving and to control fungal infection. Analysis of the 28 S rRNA gene (accession KT149770) aligned the isolate with members of the genus Apophysomyces and the pathogen was identified as Apophysomces variabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The patient left against medical advice before specific antifungal therapy could be instituted and eventually underwent below-knee amputation of the right leg at another city hospital a week later. Such devastating outcomes of Apophysomyces infection have also been reported by Pamidimukkala et al [12] and Al-Zaydani et al [23], thereby emphasizing the importance of early diagnosis and aggressive treatment in such cases.…”
Section: Discussionmentioning
confidence: 53%
“…The patient left against medical advice before specific antifungal therapy could be instituted and eventually underwent below-knee amputation of the right leg at another city hospital a week later. Such devastating outcomes of Apophysomyces infection have also been reported by Pamidimukkala et al [12] and Al-Zaydani et al [23], thereby emphasizing the importance of early diagnosis and aggressive treatment in such cases.…”
Section: Discussionmentioning
confidence: 53%
“…There are few cases of A. variabilis infection reported in the literature, mostly form India [7] , [8] , [9] , [10] , [11] , [13] , [15] , [16] ( Table 1 ). The number of cases is likely to be underestimated because A. variabilis does not produce spores readily in traditional mycological culture media used in clinical laboratories, has special nutritional requirements, grows at high temperatures (37–42 °C) and after prolonged periods of incubation (7–10 days) [9] .…”
Section: Discussionmentioning
confidence: 99%
“…From literature search and meticulous study selection process, 89 studies were included in this systematic review with data retrieved from additional 250 cases of mucormycosis due to Apophysomyces species 5,9–96 (Figure 1). The worldwide distribution of reported cases of mucormycosis due to Apophysomyces species is shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown the presence of Apophysomyces species in outdoor air samples and a high isolation rate of the fungus from Indian soil with low nitrogen content 4,98 . Besides India, the disease has been reported from other tropical and subtropical regions of the world, including Afghanistan, 29 Sri Lanka, 35 Japan, 80 Australia, 12,26,46,56,79,85,94 and parts of South East Asia, 31,32,71 Middle East, 23,24,34,36,43,45,69 Europe 33,37,88 and Central and South America 11,25,28,39,50,64,72,83 …”
Section: Discussionmentioning
confidence: 99%